How genome editing changed the world of large animal research - Fischer, Konrad; Schnieke, Angelika (Frontiers in Genome Editing, 2023)
The first genetically modified large animals were generated in 1985 by microinjection to increase the growth of agricultural livestock such as pigs(1). Since then, it has been a somewhat rocky road due to the lack of genetic tools. While methods and technologies were developed quickly for the main experimental mammal the mouse e.g. efficient pronuclear microinjection, gene targeting in embryonic stem cells and omic data, most of it was -and in part still is -lacking when it comes to livestock. Over the next decades progress in genetic engineering of large animals was driven less by research for agriculture but for biomedical applications such as the production of pharmaceutical proteins in the milk of sheep, goat, or cow, xeno-organ transplantation and modelling human diseases. Available technologies determined if a desired animal model could be realized, and efficiencies were generally low. Presented here is a short review of how genome editing tools and specifically CRISPR/Cas have impacted the large animal field in recent years. While there will be a focus on genome engineering of the pig for biomedical applications, the general principles and experimental approaches also apply to other livestock species or applications.